Voyager par l’image : la topographie dans la collection de Jehannin de Chamblanc (1722-1797) - Johanna Daniel (Les Cahiers de l'École du Louvre)
In the eighteenth century, engraved topographical views were particularly successful: by providing images of urban areas, they served as a medium for geographical knowledge in the same way as travel literature and cartography. In the second half of the century, the Dijon-born Jehannin de Chamblanc (1722–1797) put together a collection of almost 1,400 city views to form a visual inventory of contemporary urban Europe. His portfolios contained images of varying nature and quality, in which the criterion of aesthetic quality does not seem to take precedence. This article examines the collector’s acquisition and organisational strategies, examining the value he placed on these images.